ESD Design for Analog Circuits - Vashchenko, Vladislav A.; Shibkov, Andrei; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
ESD Design for Analog Circuits covers many challenging topics related to analog circuit design for both ESD device and ESD circuits at the network level. The chapters cover technical material on seven different hierarchical levels starting from elementary semiconductor structures, ESD device and clamp levels up to ESD protection network design followed by complex case studies for analog circuit design examples. Included is an extensive discussion of ESD design aspects for analog design for signal path products covering both major principles and specific case studies for DC-DC buck/boost converters, level shifters, digital-analog converters, high speed and precision power amplifiers, interface applications and system level protection. At the same time, the authors introduce a novel companion study tool for ESD protection solutions. Quick-start learning is combined with in-depth understanding for the whole spectrum of cross-disciplinary knowledge needed for excelling in the ESD field. The material combines textbook material with optional numerical simulation experience. Instructions for obtaining the simulation examples and trial version of DECIMMTM software can be found on the book's companion website www.analogesd.com. The simulation examples prepared by the authors support the specific examples discussed across the book chapters. ESD Design for Analog Circuits is a useful reference for device engineers and circuit designers addressing Analog IC Design problems.
Conductivity Modulation in Semiconductor Structures Under Breakdown and Injection -- Standard and ESD Devices in Integrated Process Technologies -- ESD Clamps -- ESD Network Design Principles -- ESD Design for Signal Path Analog -- Power Management Circuits$1 (BESD Protection -- System-Level and Discrete Components ESD.s
Keywords: Engineering; Electronics; Systems engineering; Engineering; Circuits and Systems; Electronics and Microelectronics, Instrumentation